2017
DOI: 10.1002/cbf.3312
|View full text |Cite
|
Sign up to set email alerts
|

Diethylstilbestrol regulates mouse gubernaculum testis cell proliferation via PLC‐Ca2+‐CREB pathway

Abstract: Environmental estrogens remain a serious threat to male reproductive health, and it is important to understand the mechanism by which EEs affect the male productive system. Here we explore potential mechanisms how the proliferation and contractility of gubernaculum testis cells are regulated by diethylstilbestrol. Our findings provide the first evidence that PLC-Ca -CREB signalling pathway mediates the nongenomic effects of diethylstilbestrol on gubernaculum testis cells. These findings provide new insight int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…It has been reported that intracellular Ca 2+ levels contribute to the activation of CREB [ 39 – 41 ]. Activation of CREB, in turn, enhances proliferation and migration in ASM cells [ 42 , 43 ], which may indicate a role for CREB in airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that intracellular Ca 2+ levels contribute to the activation of CREB [ 39 – 41 ]. Activation of CREB, in turn, enhances proliferation and migration in ASM cells [ 42 , 43 ], which may indicate a role for CREB in airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BPA has been shown to promote migration, invasion, metastasis, proliferation, and cell transformation in lung, colon, and breast cancer cells, as well as in mammalian cells [211][212][213]. Similarly, DES has been shown to regulate cell proliferation in testis [214] and melanoma cells [215]. Another link between estrogens and tumor development arises from accumulating evidence reporting that estrogenic substances induce defects of the centrosome and w-CIN, which may contribute to tumor formation [17,20,216].…”
Section: Impact Of Estrogens On Human Diseases and Cancermentioning
confidence: 99%
“…The cell pellet was added to DMEM containing charcoal-stripped FBS (CS-FBS) (Invitrogen, USA) but lacking estrogen (10% v/v), aerated to create a single-cell suspension, seeded into a 25-ml culture flask, and incubated in a 5% CO 2 incubator at 37 °C with saturated humidity [ 20 , 21 ]. Cells were randomized into groups consisting of control group, INSL3 group (cells treated by 0.02 ng/ml INSL3), U73122 (Phospholipase C (PLC) inhibitor) group (cells pretreated by 1 μmol/L U73122) and INSL3 + U73122 group (cells pretreated by 1 μmol/L U73122 for 10 min, then treated by 0.02 ng/ml INSL3) [ 19 , 20 ]. The gubernacular cells were treated with INSL3 for 48 h, and the mouse INSL3 was from Phoenix Pharmaceutics.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have confirmed that the protein kinase C (PKC) signaling pathway plays an important role in intercellular signal transport, transcriptional regulation of cell function, opening/closing of an ion channel, and energy metabolism, and it can regulate cell proliferation, differentiation, contraction, secretion and metabolism [ 15 18 ]. In a previous study on the effect of diethylbestrol (DES) on mouse gubernacular cells, it was found that DES regulated the proliferation of mouse gubernacular cells through the PLC‐Ca 2+ ‐CREB pathway [ 19 ]. These data suggest that the PLC/PKC pathway may mediate biological functions in gubernacular cells.…”
Section: Introductionmentioning
confidence: 99%